Biofilm-mediated immune dysregulation in chronic pulmonary diseases: mechanisms and clinical implications - Yu, Xiao; Zhang, Yidan; Yao, Yiwen; Cho, William C.; Shang, Anquan (Frontiers in Microbiology, 2026)
Microbial biofilms are increasingly recognized as critical modulators of chronic airway inflammation and immune dysregulation in pulmonary diseases. This review summarizes current evidence on how biofilm formation and persistence alter host immune responses, contributing to the pathogenesis of chronic lung disorders. We first outline the characteristics of respiratory biofilms and the major pathogens involved. We then discuss how biofilms reshape innate and adaptive immunity—impairing pattern recognition receptor signaling, promoting neutrophil extracellular trap (NET) formation, altering macrophage polarization, and skewing T-cell differentiation. These immune alterations sustain low-grade inflammation, tissue remodeling, and immune tolerance, driving disease progression in chronic obstructive pulmonary disease, bronchiectasis, severe asthma, and even lung cancer. We further highlight emerging diagnostic biomarkers and therapeutic approaches targeting biofilm-associated immune pathways, including combined antibiofilm and immunomodulatory strategies. Finally, we identify key knowledge gaps and propose future research directions, emphasizing multi-omics approaches and personalized interventions to better define and target biofilm-driven immune dysregulation in chronic respiratory diseases.